2008
DOI: 10.3132/pcrj.2009.00001
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the response to postal questionnaire surveys about respiratory symptoms

Abstract: Background: Response rates to postal questionnaires have been falling in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
7
24
1
2
Order By: Relevance
“…However, women were more often able to report their waist circumference and waist hip ratio. It has previously been shown that women are more willing to respond to questionnaires overall [59][60][61], and this might also apply to response pattern of individual questions.…”
Section: Discussionmentioning
confidence: 98%
“…However, women were more often able to report their waist circumference and waist hip ratio. It has previously been shown that women are more willing to respond to questionnaires overall [59][60][61], and this might also apply to response pattern of individual questions.…”
Section: Discussionmentioning
confidence: 98%
“…There was no important association between respiratory symptoms, and associated feature prevalence and stage of response. 21 However, if those who are most ill are least capable and therefore least likely to respond to repeated surveys (or indeed to any postal survey), the resulting response bias would in fact cause an underestimate of the decrease in HRQoL. Ceiling effects on EQ-5D (particularly due to the modelling algorithm for calculating EQ-5Dindex), as reported elsewhere, [22][23][24] may also have contributed to this potential underestimate.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Although the group included in the analyses was older and contained fewer smokers than the subjects excluded, the results were adjusted for these potential confounders. Response rates to the postal analysis from another paper 21 [2004]). Early responders were older, and more likely to be female, but less likely to smoke than those who responded to reminders.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Diversos trabajos han investigado las características (sociodemográficas, hábitos de salud, estado de salud autopercibida) de los respondedores en comparación con quienes no responden y el posible efecto de las diferentes características sobre la validez de los resultados de una encuesta de base poblacional, con conclusiones divergentes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Algunos autores consideran que la influencia de la no respuesta es poco relevante sobre los resultados, siendo estos extrapolables a la población general 12,[14][15][16][17]23 .…”
Section: Introductionunclassified
“…Algunos autores consideran que la influencia de la no respuesta es poco relevante sobre los resultados, siendo estos extrapolables a la población general 12,[14][15][16][17]23 . Sin embargo, otros sugieren que la no respuesta se asocia de forma significativa con un nivel socioeconómico y educativo más bajo, peor perfil de salud y peores estilos de vida que la respuesta, representando una amenaza potencial a la validez externa de las estimaciones obtenidas en la encuesta 9,10,13,[18][19][20][21][22] .…”
Section: Introductionunclassified